Modeling of the van der Waals forces during the adhesion of capsule-shaped bacteria to flat surfaces - Mohamed Zuki, Fathiah (MDPI, 2021)
A novel model is developed to evaluate the van der Waals (vdW) interactions between a capsule shaped bacterium (P. putida) and flat minerals plates in different approach profiles: Vertically and horizontally. A comparison of the approaches to the well-developed spherical particle to mineral surface (semi-infinite wall and spherical) approach has been made in this investigation. The van der Waals (vdW) interaction potentials for a capsule-shaped bacterium are found using Hamaker’s microscopic approach of sphere to plate and cylinder to plate either vertically or horizontally to the flat surface. The numerical results show that a horizontal orientated capsule shaped bacterium to mineral surface interaction was more attractive compared to a capsule shaped bacterium approaching vertically. The orientation of the bacterial approaching a surface as well as the type and topology of the mineral influence the adhesion of a bacteria to that surface. Furthermore, the density difference among each type of bacteria shape (capsule, cylinder, and sphere) require different amounts of energy to adhere to hematite and quartz surfaces. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.